Evolución del mercado laboral agrícola: hacia una tipología de jornaleros para Jalisco - Salgado-Viveros, Cecilia; Stabridis, Omar (El Colegio de México, 2024)
Since the 1970s, the Mexican countryside has undergone a process of de-peasantization, which has significantly impacted its most vulnerable sector: agricultural day laborers. This shift has exacerbated their labor precariousness and social vulnerability, leading to increased labor migration to agricultural export states. In order to analyze the levels of precariousness and vulnerability experienced by agricultural day laborers, the objective of this article is to construct a typology for this group in the state of Jalisco, based on ethnographic results and latent class analysis using the 2020 census sample. The findings reveal five distinct classes of laborers, each displaying variations in wages, precariousness, and vulnerability. This typology can be replicated in other regions or countries with similar agricultural structures.